Endocrine disruption: Reproductive toxicity of glyceryl trinitrate and isosorbide mononitrate in male Wistar rats. (1st June 2022) - Sharif, Zumna; Akhtar, Muhammad Furqan; Sharif, Hamna; Saleem, Ammara; Khan, Muhammad Imran; Riaz, Amjad
Abstract: Glyceryl trinitrate (GTN) and isosorbide mononitrate (IM) are organic nitrates which release nitric oxide upon metabolism with potential to adversely affect male reproductive function. Therefore, this study was designed to evaluate the sub‐chronic effect of these organic nitrates on reproductive system in male rats. Wistar rats were separately treated with GTN and IM at 2.5, 5 and 7.5 mg/kg/day by oral gavage for 45 days. At the end of treatment, serum blood samples were taken from anaesthetized rats for assessment of hormonal profile. Epididymis was removed to analyse sperm parameters. Rat testes were dissected to perform histopathological evaluation and oxidative stress biomarkers. The GTN and IM treated groups showed a significant decrease in sperm parameters (count, motility and viability) and serum testosterone in comparison to normal control group. The GTN and IM treatment also altered sperm morphology such as bent tail and head deformities as compared to control. A significant decrease in catalase activity and, increase in nitric oxide and malondialdehyde were observed in high dose drug treated groups. Moreover, a significant increase in follicle stimulating hormone and decrease in testosterone levels were evident in all drug treated groups. The level of luteinizing hormone was raised in rats treated with medium doses of drugs while it decreased at the highest dose of both drugs. Histological study showed vacuolization and degeneration of seminiferous tubules. It is concluded that GTN and IM treatment adversely affected the male reproductive function by altering sperm parameters and disrupting the reproductive hormone profile which may be attributed to the increased level of nitric oxide and oxidative stress.